A business model for mobile commerce applications using multimedia messaging service. (6th May 2010) - Samanta, Swadesh Kumar; Woods, John; Ghanbari, Mohammed
The current adoption of Multimedia Messaging Service (MMS) by mobile consumers is far below that predicted when it was initially conceived. There are potentially a number of reasons for this, but most of the research focuses on the growth of person-to-person MMS messages and identifies the high price as the main deterrent. Drawing similarities from two-sided markets in the literature, we present a business model where the mobile operator and the handset manufacturer jointly subsidise the cost of the handset and generate revenue from mobile commerce (m-commerce) applications. The model suggests that an improvement in the current mobile MMS delivery mechanism is required. We show that the improvement can facilitate the introduction of m-commerce applications such as auctions, sale of perishable goods/services, and sale/delivery of multimedia content (e.g., digital music, movie songs and movie clips) through the mobile phone. The model has the potential to generate additional revenue for the operator via applications such as mobile advertisement.